Improving State Economic Policy in the Context of the Transition to Green Growth - POPOK, Leonid; KARPENKO, Elena; VORONKOVA, Olga; KOVALEVA, Irina; ZAVYALOV, Mikhail; FEDOROV, Boris (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019, 2020)
The article discusses the issue of improving state economic policy in the context of the transition to "green" growth. Until recently, the “green” economy was often viewed as a part of the economy associated only with the production of environmental goods and services. The term “green business” is often used here. The modern approach to the transition to a green economy should consider the entire economy, all its sectors and activities. You can make a "green" part of the economy. However, such an economy will not be sustainable and will degrade over time. However, until very recently, the consideration of environmental problems was carried out mainly at the microeconomic and local levels. The theory has paid minimal attention to the inclusion of the environmental factor in the macroeconomy or the global economy, which has become one of the important causes of environmental crises in individual countries and in the world.